The Role of Daily English Conversation in Developing Students' English Communication Skills in a Boarding School Environment: Penelitian - Muhammad Fathan Hasyraf; M. Kenzie Aryasatya; Muhammad Dhafin Nurfaiq Lubis; Rifqi Islamy Simarmata; Mhd Fahri Arrowi Pane; M. Naufal Azmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
English communication skills are essential competencies for students in the era of globalization, yet many learners still experience limited opportunities to practice spoken English actively. One approach considered effective in addressing this issue is language habituation through the Daily English Conversation program, particularly within a boarding school environment that supports continuous language exposure. This study aims to describe the implementation of the Daily English Conversation program and its role in developing students’ English communication skills at Jabal Rahmah Mulia Boarding School. This research employed a qualitative descriptive approach. The participants consisted of 24 eleventh-grade students who actively participated in the program and 4 English teachers responsible for its supervision. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that the Daily English Conversation program is implemented consistently through English Area policies, daily conversational practices, and intensive interaction in the boarding school environment. Teachers and coaches play a crucial role as facilitators, language models, and providers of corrective feedback. The program contributes significantly to the improvement of students’ speaking and listening skills, as reflected in increased fluency, confidence, and comprehension in daily communication. Furthermore, supporting activities such as Friday Speech and the English Festival strengthen students’ public speaking abilities and motivation to use English in both informal and formal contexts. Therefore, Daily English Conversation serves not only as a medium for enhancing students’ English communication skills but also as an effective strategy for fostering positive attitudes and readiness to communicate in English within a boarding school setting.